Student perceptions of U.S. based school day physical activity best practices in relation to accelerometer-based sedentary behavior and activity - Ann Pulling Kuhn; Ajuni Choudhary; Amy Zemanick; Hannah Lane; Bridget Armstrong; Yan Wang; Rachel Deitch; Erin R. Hager (Preventive Medicine Reports)
Objective: To examine associations between student perceptions of school physical activity best practices and accelerometer-based physical activity during school days. Methods: The sample was 758 students in grades 3rd-4th or 6th–7th (female-58 %; 31 % Black/African American) from 33 schools across five school districts in a Mid-Atlantic state in the U.S. Students completed the Perceptions of the Environment at School survey to assess perceived implementation of 11 school physical activity best practices and wore an Actical ankle accelerometer for 7 days between 2017 and 2019. Accelerometer cutpoints were applied for percent time in sedentary, light, and moderate-vigorous physical activity (MVPA) during school hours. Adjusted mixed effects linear regression models were used to predict percent time in each physical activity category, with separate models for elementary and middle school. Results: More best practices were perceived by elementary versus middle schoolers (sum score = 3.3 versus 1.5, p < .01). For every additional best practice perceived, elementary schoolers spent 0.64 % less time in sedentary behavior (B = -0.62; SE = 0.27, p = .02), equivalent to ∼12 fewer minutes/week in sedentary behaviors, and 0.58 % more time in light activity (B = 0.58; SE = 0.25, p = .02; ∼10 more minutes/week). No associations observed for middle schoolers or MVPA. Conclusions: Few best practices were perceived as being implemented in school. Elementary schoolers who perceived more best practices spent more time in light activity and less in sedentary behavior, but this relationship was not found among middle schoolers. Future research should promote implementation of school physical activity best practices and examine the linkage between implementation, student perceptions, and behavior change.Trial Registration: Clinical Trials, NCT03432715; Registered on 02/2/2018.